2023
DOI: 10.3389/fimmu.2022.1006639
|View full text |Cite
|
Sign up to set email alerts
|

The association of BTLA gene polymorphisms with non-small lung cancer risk in smokers and never-smokers

Abstract: IntroductionLung cancer is the predominant cause of death among cancer patients and non-small cell lung cancer (NSCLC) is the most common type. Cigarette smoking is the prevailing risk factor for NSCLC, nevertheless, this cancer is also diagnosed in never-smokers. B and T lymphocyte attenuator (BTLA) belongs to immunological checkpoints which are key regulatory molecules of the immune response. A growing body of evidence highlights the important role of BTLA in cancer. In our previous studies, we showed a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Andrzejczak et al found that rs1982809 variant was significantly related to non-small cell lung cancer risk. 30 Karabon et al reported that rs1982809, rs9288953 variants would affect the susceptibility to chronic lymphocytic leukemia. 31 It was worth noting that rs9288953 variant was found to be significantly associated with the development of drug resistance among PTB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Andrzejczak et al found that rs1982809 variant was significantly related to non-small cell lung cancer risk. 30 Karabon et al reported that rs1982809, rs9288953 variants would affect the susceptibility to chronic lymphocytic leukemia. 31 It was worth noting that rs9288953 variant was found to be significantly associated with the development of drug resistance among PTB patients.…”
Section: Discussionmentioning
confidence: 99%
“…In one of our studies by Andrzejczak et al we investigated the correlation between seven BTLA SNPs: rs2705511, rs1982809, rs9288952, rs9288953, rs1844089, rs11921669, and rs2633582, and susceptibility to NSCLC in 383 cases and 474 HC in the Polish population. It was found that the rs1982809 SNP was associated with NSCLC risk, where carriers of the rs1982809 G allele were more frequent in NSCLC patients compared to HC [ 122 ]. Our results were consistent with Khadhraoui’s study [ 121 ].…”
Section: Btla Gene Variants and Cancermentioning
confidence: 99%
“…In addition, haplotype global distribution differed between never-smokers and smokers, where CGACG, CGATG, and AGGCA (rs2705511, rs1982809, rs9288952, rs9288953, rs1844089) haplotypes were more frequent in never-smokers. After stratification by gender, females carrying the rs1982809 G allele or the rs9288953 T allele had a higher risk of NSCLC by 1.6 and 2.2 times, respectively When disease stage was taken in to consideration, rs1982809 G and rs2705511 C alleles were associated with the more advanced stages of NSCLC (stage II and III), but not with stage IV [ 122 ]. Moreover, similarly to Khadhraoui’s study [ 121 ], we noticed a higher risk of adenocarcinoma in patients bearing the rs1982809 AG genotype.…”
Section: Btla Gene Variants and Cancermentioning
confidence: 99%
See 2 more Smart Citations